Permanence, stability, continuity. Terminological remarks - Janowska, Aleksandra (Philology as the Ordering of Chaos: Language and Text Studies. Ad honorem Professoris Marci Cybulski, 2018)
Interest in the things which are permanent (stable) in language, and therefore, according to a general belief, in the things which are static in diachrony, came along with a reflection about the phenomenon of the permanence of language. Contrary to appearances, this theme continues to be a source of many interpretative problems. The author is interested above all in the basic problems associated with what this permanence (stability) is and whether this phenomenon is actually homogenous or not. She directs the reader’s attention to a certain terminological and conceptual confusion, for on the one hand, in linguistic research works the following terms are used synonymously: permanence, stability, duration, continuity — in reference to the same concepts, and on the other hand, the same term is applied to heterogeneous phenomena.